Association Between Design Elements of Concussion Laws and Reporting of Sports-Related Concussions Among US High School Athletes, 2009-2017. (November 2021) - Yang, Jingzhen; Harvey, Hosea H.; Sullivan, Lindsay; Huang, Lihong; Dawn Comstock, R.
Objectives: Studies that evaluate the effectiveness of concussion laws often use only a single variable (ie, presence of the law), failing to account for law complexity. We examined the association between multiple design elements of state concussion laws and rates of sports-related concussion reporting among US high school athletes. Methods: We derived 3 design elements of concussion laws from the 2009-2017 LawAtlas database: (1) strength of law, (2) number of law revisions, and (3) speed of law adoption. We examined the association between these design elements and rates of new and recurrent sports-related concussion reporting from the 2009-2010 through 2016-2017 academic years in a nationally representative sample of high school athletes participating in High School Report Information Online, an online data collection tool. Results: A total of 7064 sports-related concussions (6332 [89.6%] new and 732 [10.4%] recurrent concussions) were reported during the study period, with an overall rate of 39.7 sports-related concussions per 100 000 athletic exposures (eg, game or practice). Rates of new concussion reporting were higher among high schools in states with medium- or high-strength concussion laws than in states with low-strength concussion laws and in states with at least 1 concussion law revision than in states with no concussion law revisions. Rates of recurrent concussion reporting were lower among high schools in states with ≥2 concussion law revisions than in states with <2 concussion law revisions. Early law adoption was associated with higher rates of new and recurrent concussion reporting, and late law adoption was associated with lower rates of new and recurrent concussion reporting. Conclusion: Our findings may help inform legislators of the public health effect of concussion laws.